Aging, Social Security Design, and Capital Accumulation - Antoine Dedry; Harun Onder; Pierre Pestieau (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper analyzes the impact of demographic aging on capital accumulation and welfare in economies with unfunded pensions. Using a two-period overlapping generation model with potentially endogenous retirement decisions, it shows that both the type of aging, i.e. declining fertility or increasing longevity, and the type of pension system, i.e. defined contributions or defined benefits, are important in understanding this impact. Results show that when aging is driven by increasing longevity, an unregulated retirement age system leads to a greater improvement in welfare. In contrast, with decreasing fertility, a mandatory retirement system with defined contributions fares better.
Keywords: H20; F42; H80; 330; aging; public finance sustainability; social security